UNLOCKING EMPLOYEE GREEN BEHAVIOR: A MULTILEVEL INVESTIGATION OF PERCEIVES CSR, ORGANIZATIONAL IDENTIFICATION AND GREEN HRM - Mahreen Bashir; Dr.Ayesha Saba; Dr.Muhammad Farooq Akhtar (International Journal of Contemporary Issues in Social Sciences, 2024)
Organizations find it difficult to stop environmental degradation and harm in the modern, globalized world because they are the main causes of this ecological degradation. The focus of researchers in the domain of sustainable growth and organizational behavior has been on how perceived corporate social responsibility (CSR) influences employee green behavior (EGB). Despite some early efforts, no concrete antecedents and processes have been documented in this growing discipline. Thus, by investigating how and under what circumstances perceived CSR influences EGB, this study contributes to the current debate in this area. This research investigates the impact of perceived CSR on EGB by the mediation mechanism of organizational identification (OID) and moderation of green HRM. The social exchange theory is employed in this study to develop hypotheses. In this investigation empirical analysis of the underlying framework is conducted by collecting multilevel data in two phases with time-based breaks from 415 employees of 83 stock exchange listed firms. Using Mplus, we performed multilevel path analysis and verified a significant favorable effect of perceived CSR on OID, which in turn leads to EGB. Furthermore, the contingency of green HRM enhances the indirect effect of perceived CSR on EGB via the mediation of OID. Current research uncovers a number of techniques that firms may use to strategically target employee green behavior.